Design of High-Order Iterative Methods for Nonlinear Systems by Using Weight Function Procedure - Santiago Artidiello; Alicia Cordero; Juan R. Torregrosa; María P. Vassileva (Abstract and Applied Analysis)
We present two classes of iterative methods whose orders of convergence are four and five, respectively, for solving systems of nonlinear equations, by using the technique of weight functions in each step. Moreover, we show an extension to higher order, adding only one functional evaluation of the vectorial nonlinear function. We perform numerical tests to compare the proposed methods with other schemes in the literature and test their effectiveness on specific nonlinear problems. Moreover, some real basins of attraction are analyzed in order to check the relation between the order of convergence and the set of convergent starting points.